2020
DOI: 10.1186/s12913-020-05123-7
|View full text |Cite
|
Sign up to set email alerts
|

Patient Centred Medical Home (PCMH) transitions in western Sydney, Australia: a qualitative study

Abstract: Background Patient Centred Medical Homes (PCMHs), increasingly evidenced to provide high quality primary care, are new to Australia. To learn how this promising new healthcare model works in an Australian setting we explored experiences of healthcare providers in outer urban Sydney, where a number of practices are transitioning from traditional Australian general practice models to incorporate elements of PCMH approaches. Methods We collected quali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(59 citation statements)
references
References 26 publications
2
57
0
Order By: Relevance
“…On the other hand, in Australia, misalignment of funding with PCMH goals discourages GP practices from transforming to PCMH [17]. In simple words, no matter how attractive PCMH might appear as a model of care, GP practices will not transform to it if they must sacrifice their livelihood [16,17]. However, according to our study findings, some FMC GPs felt that funding possibly weakened GPs intrinsic motivation to make FMC's operation more efficient.…”
Section: Establishment and Developmentmentioning
confidence: 64%
See 4 more Smart Citations
“…On the other hand, in Australia, misalignment of funding with PCMH goals discourages GP practices from transforming to PCMH [17]. In simple words, no matter how attractive PCMH might appear as a model of care, GP practices will not transform to it if they must sacrifice their livelihood [16,17]. However, according to our study findings, some FMC GPs felt that funding possibly weakened GPs intrinsic motivation to make FMC's operation more efficient.…”
Section: Establishment and Developmentmentioning
confidence: 64%
“…Only a handful of studies have explored the broader contextual policy factors affecting PCMHs' implementation [12][13][14][15][16][17]. For example, studies [12,[14][15][16][17] reported misalignment of practice payment models with PCMH strategies and lack of funding as factors impeding practices to transform to PCMHs. Additionally, studies [16,17] identified workforce policy issues and the need for developing shared vision as factors hindering and facilitating PCMH transformation, respectively.…”
Section: Patient-centered Medical Homementioning
confidence: 99%
See 3 more Smart Citations